Founder Replacement and Startup Performance - Ewens, Michael; Marx, Matt (Review of Financial Studies, 2018)
We provide causal evidence that venture capitalists (VCs) improve the performance of their portfolio companies by replacing founders. Using a database of venture capital financings augmented with hand-collected founder turnover events, we exploit shocks to the supply of outside executives via 14 states’ changes to non-compete laws from 1995 to 2016. Naive regressions of startup performance on replacement suggest a negative correlation that may reflect negative selection. Indeed, instrumented regressions reverse the sign of this effect, suggesting that founder replacement instead improves performance. The evidence points to the replacement of founders as a specific mechanism by which VCs add value.